Organic fertilizer enhances rice growth in severe saline–alkali soil by increasing soil bacterial diversity - Zhang, Zhengkun; Liu, Hong; Liu, Xiaoxiao; Chen, Yong; Lu, Yang; Shen, Minchong; Dang, Keke; Zhao, Yu; Dong, Yuanhua; Li, Qiyun; Li, Jiangang (Soil use and management, 2022)
The northeast region of China is an important grain‐growing area. However, severe soil salinization in the region impairs plant production. In the present study, organic fertilizer application (composted poultry manure) was evaluated as a potential strategy for remediating saline–alkali soil and promoting rice growth. Following continuous organic fertilizer application for 4 years, the contents of basic cations, including sodium (Na+) and chlorine cations (Cl−), decreased significantly (p < .05) (soil Na + decreased from 24.3 mg kg−1 to 21.8 mg kg−1 and soil Cl‐ decreased from 570.4 mg kg−1 to 38.5 mg kg−1), while soil organic matter (SOM), total nitrogen (TN), total phosphorus (TP), available nitrogen (AN) and available potassium (AK) were markedly increased (especially for soil AK, which increased from 85.8 mg kg−1 to 141.7 mg kg−1) compared to the treatment without organic fertilizer application. In addition, the relative abundance of plant growth‐promoting bacteria such as Thiobacillius, Methylobacter, Rhodoferax, Lysobacter and Flavobacterium increased significantly, whereas halophilic genera (Nitriliruptor, Mongoliicoccus, Litoribacter, Halomonas and Aliidiomarina) decreased markedly. Bacterial diversity also increased significantly, with data analysis suggesting that such shifts translated into more abundant plant‐growth‐related gene functions. According to structural equation modelling results, soil bacterial diversity was a key factor driving the maintenance of healthy plant growth in saline–alkali soil. These results suggested that organic fertilizers could improve the physicochemical properties of saline–alkali soil by altering interactions between rice plants and bacteria, for example, via the recruitment of specific beneficial microbial communities to increase their salinity–alkali stress tolerance, and, in turn, promote their growth.